Effects of intake of breakfast or caffeine‐containing beverages on measurement of circulating chromogranin A in plasma. Issue 1 (15th November 2018) - Robbins, Helen L.; Symington, Megan; Mosterman, Barbara; Tranter, Fiona; Davies, Louise; Randeva, Harpal S.; Penedo, Ana; Ferreira, Clara; Darby, Catherine; Grammatopoulos, Dimitri; Kaltsas, Gregory; Weickert, Martin O.
Summary: Context: Sampling in the nonfasted state might result in false‐high measurements of plasma chromogranin A (CgA), a key biomarker for patients with gastro‐entero‐pancreatic neuroendocrine neoplasms (GEP‐NENs). Objective: To investigate whether intake of a 5‐item English breakfast together with tea/coffee (Bfast‐T/C) or intake of tea/coffee (T/C) alone relevantly influences postprandial CgA in GEP‐NENs and controls. Methods: In a randomised, controlled, double crossover study, we investigated in >10‐hour overnight fasted individuals the effects of Bfast‐T/C vs T/C vs the ongoing fasted state on 180‐minute postprandial plasma CgA concentrations (28 patients with GEP‐NENs, of those 22 on treatment with long‐acting somatostatin analogues (SSA); and 11 controls). Ten participants (8 GEP‐NEN, 2 controls) were on treatment with proton pump inhibitors (PPI). Results: Intake of Bfast‐TC but not T/C alone increased CgA in the pooled cohort, reflecting the situation in screening, from 90 minute [area under the curve (AUC)CgA0 ‐180 minute, ongoing fasted 172.6 ± 4.6 vs T/C 173.3 ± 5.2 vs Bfast‐TC 204.2 ± 7.9, P  = 0.0002]. Postprandial responses to Bfast‐T/C in controls and GEP‐NENs were comparable. PPI usage was associated with markedly increased fasted CgA in the pooled cohort (429.3 ± 90.4 vs 91.0 ± 14.7 µg/L; P  < 0.0001). AUCCgA 0 ‐180 minute remained higher following Bfast‐T/C after exclusion of PPI users ( P  < 0.05). In GEP‐NENs, effects of Bfast‐T/C on postprandial CgA raises were more pronounced in patients not treated with SSA. Conclusions: Intake of Bfast‐T/C, but not T/C alone, increased postprandial CgA in both patients with GEP‐NENs and controls up to 34%. Fasted CgA measurements should be sought, if possible, and PPIs paused prior to measurement. ClinicalTrials.gov Identifier: NCT03288402.